The veiled Garvey : the life & times of Amy Jacques Garvey - Taylor, Ula Y. (Gender & American culture., 2002)
In this biography, Ula Taylor explores the life and ideas of one of the most important, if largely unsung, Pan-African freedom fighters of the 20th century: Amy Jacques Garvey (1895-1973).